Legitimacy and Political Violence: A Habermasian Perspective - Cook, Deborah (Social justice, 2003)
Part of a special section on the intersection of ideologies of violence. The writer examines Jurgen Habermas's views as they apply to the issue of legitimacy, as it has taken shape in the violent conflicts between terrorist organizations and states. She contends that there are difficulties with the Habermasian view of terrorism as a response to legitimation deficits for two reasons: firstly, he infers that terrorism has a single cause, or, at best, a set of related causes; and secondly, Habermas does not consider that terrorism has involved a far more expansive contestation of a state's claims to legitimacy.